2021
DOI: 10.1016/j.heliyon.2021.e06410
|View full text |Cite
|
Sign up to set email alerts
|

African Growth and Opportunity Act and trade performance in Nigeria

Abstract: This study examines the implementation status of the African Growth Opportunity Act (AGOA) and its performance in Nigeria using socioeconomic indicators. Also, the study provides recommendations on how Nigeria can harness the opportunities latent in AGOA using statistical inference and in-depth interview with relevant stakeholders. The findings show that despite the privileged economic relations with the United States of America (USA), Nigeria is yet to optimise the benefits derivable from the AGOA initiative.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…Nonetheless, when we incorporate these two agreements, the AGOA t showed a strong negative (−4.2) effect on REC ict and REC _ WM ict of Nigerian cocoa at a 1% level of significance. Osabohien et al (2021) revealed that Nigeria is yet to optimize the benefits derivable from the AGOA initiative. Contrarily, Sorgho and Tharakan (2019) found that AGOA has positively impacted African countries.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, when we incorporate these two agreements, the AGOA t showed a strong negative (−4.2) effect on REC ict and REC _ WM ict of Nigerian cocoa at a 1% level of significance. Osabohien et al (2021) revealed that Nigeria is yet to optimize the benefits derivable from the AGOA initiative. Contrarily, Sorgho and Tharakan (2019) found that AGOA has positively impacted African countries.…”
Section: Resultsmentioning
confidence: 99%
“…Empirical studies exploring the direct influence of AGOA on poverty are surprisingly sparse, and results from the indirect studies predominantly underscore a tenuous link between the implementation of AGOA and discernible poverty reduction [65]. Computable General Equilibrium (an economic model used to analyze the economy-wide impact of policy changes, market shocks, or other external changes)-based simulations suggest that AGOA may confer income and welfare gains for unskilled and generally poor workers [68]. Researchers also hypothesize potential poverty reduction impacts based on observed employment gains and growth effects.…”
Section: On Poverty Levelsmentioning
confidence: 99%
“…Furthermore, regional trading blocs can also play a significant role in promoting trade and economic integration. For Nigeria, the Economic Community of West African States is a regional trading bloc promoting economic cooperation and integration among its member states (Osabohien et al, 2021). Through ECOWAS, Nigeria can work towards aligning its trade policies and procedures with those of its neighboring countries, harmonizing regulations and standards, and facilitating the movement of goods and services across borders (Dynamics of Trade between Nigeria and Other ECOWAS Countries, n.d).…”
Section: Embracing Regional Trading Blocks: a Focus On Ecowas For Nig...mentioning
confidence: 99%